1983
DOI: 10.1139/v83-360
|View full text |Cite
|
Sign up to set email alerts
|

Condensed-phase reactions of O3 with NH3 and NH2OH

Abstract: The reactions of O3 with NH3 and NH2OH were studied in the condensed phase. A yellow ozonide was formed immediately upon the addition of O3 to the NH2OH solid maintained at −190 °C, but the yellow–orange ozonide seen in the NH3 case was not formed until the system was warmed to −170 °C. These ozonides could be reconverted to reactants by photolysis with near ultraviolet light or by heating to −90 °C (NH3+O3−) or −115 °C (NH2OH+O3−).Upon warming the NH3–O3 system to −130 °C, NH4NO3•3NH3 appeared. It started to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…The absence of NO -2 is also consistent with aqueous work (Equation ( 8)), where Singer & Zilli (1975) note the absence of detectable nitrite in solution despite a O 3 /NO -3 ratio of 4. Interestingly, we also observe a feature near 800 cm −1 above 90 K, which has been previously attributed to ozonide in mixtures of NH 3 and O 3 (Herman & Giguère 1965;Huston et al 1983b). While it is possible that this is ozonide, it may also be a weaker band of nitrate, as its appearance and increase correlate well with the stronger nitrate doublet absorptions at higher wavenumbers.…”
Section: Reaction Chemistry and Spectral Assignmentssupporting
confidence: 75%
See 2 more Smart Citations
“…The absence of NO -2 is also consistent with aqueous work (Equation ( 8)), where Singer & Zilli (1975) note the absence of detectable nitrite in solution despite a O 3 /NO -3 ratio of 4. Interestingly, we also observe a feature near 800 cm −1 above 90 K, which has been previously attributed to ozonide in mixtures of NH 3 and O 3 (Herman & Giguère 1965;Huston et al 1983b). While it is possible that this is ozonide, it may also be a weaker band of nitrate, as its appearance and increase correlate well with the stronger nitrate doublet absorptions at higher wavenumbers.…”
Section: Reaction Chemistry and Spectral Assignmentssupporting
confidence: 75%
“…Unlike the studies mentioned above, which examined this chemical system at or near room temperature, Huston et al (1983b) found that a reaction between NH 3 and O 3 also occurs readily at cryogenic temperatures in the solid phase. This reaction produced NH 4 NO 3 in the presence of excess NH 3 through the intermediate ammonia ozonide ( + NH 3 O -3 ), which was identified based on an IR absorption band at 800 cm −1 and a yellow color change:…”
Section: Reaction Chemistry and Spectral Assignmentsmentioning
confidence: 68%
See 1 more Smart Citation
“…Th e reaction kinetics NH 3 -O 3 producing NH 4 NO 3 were studied in a water solution (Hoigné, Bader 1978) in the gas stage (Olszyna, Heicklen 1972) as well as in the condensation stage (Huston et al 1983). If ozone and ammonia react in the gas stage at room temperature, the majority of the products are NH 4 NO 3 , O 2 and H 2 O, produced according to the noted Eq.…”
mentioning
confidence: 99%